Intervenciones psicológicas para la inclusión educativa de las diversidades identitarias - Chero Briones, Damián Andrés (My University, 2020)
Identity diversities are defined as the multiplicity of behaviors, emotions, affects and sexual manifestations related to a gender identity or sexual orientation. It is not always possible to understand these types of identities in the family, in schools and colleges, as they escape the social norms proposed by the heteropatriarchy. This produces violent reactions towards the LGBTI community, causing difficulties in the different areas of academic and social development. Reliable information is collected to learn about gender studies and, as is the case with this trial, homophobic and transphobic behaviors executed in the educational setting. It is concluded that this exclusion has arisen due to the heteronormative discourse developed historically in different aspects of daily life that is manifested with concrete derogatory actions and this is reflected in the disapproval and discrimination suffered by this population, in the family, in social and interpersonal relations and in the educational aspect. This essay also specifies the psychological interventions to be applied for educational inclusion, with emphasis on teachers, who execute discriminatory actions causing discomfort in the students that make up this identity population. It points out the case exposed in the biographical book, Yo nena, Yo princesa by the author Gabriela Mansilla, which tells the story of the first trans girl who accesses her ID card under the protection of the Gender Identity Law in Argentina. It considers relevant aspects about the school life of this minor and the process she went through to build her identity.
Las diversidades identitarias se las define como la multiplicidad de conductas, emociones, afectos y manifestaciones sexuales relacionados a una identidad de género u orientación sexual. No siempre en la familia, en la escuelas y colegios, se logra comprender sobre este tipo de identidades, que escapan de la normativa social propuesta por el heteropatriarcado, lo que produce reacciones violentas hacia la comunidad LGBTI, ocasionando dificultades en las distintas áreas de desenvolvimiento académico y social. Se recopila información confiable para conocer de los estudios de género y, como es el caso de este ensayo, conductas homofóbicas y transfóbicas ejecutadas en el ámbito educativo. Se concluye que esta exclusión, ha surgido por el discurso heteronormativo desarrollado históricamente en distintos aspectos de la vida cotidiana que se manifiesta con acciones despectivas concretas y esto se ve reflejado en la desaprobación y discriminación que padece esta población, en la familia, en las relaciones sociales, interpersonales y aspecto educativo. Este ensayo también especifica las intervenciones psicológicas a aplicarse para la inclusión educativa, con énfasis en los docentes, que ejecutan acciones discriminatorias ocasionando malestar en los estudiantes que conforman esta población identitaria. Se puntualiza el caso expuesto en el libro biográfico, Yo nena, Yo princesa de la autora Gabriela Mansilla, que relata la historia de la primera niña trans que accede a su DNI bajo el amparo de la Ley de identidad de género en Argentina. Se consideran aspectos relevantes acerca de la vida escolar de esta menor y el proceso que atravesó para construir su identidad.
Keywords: INCLUSION EDUCATIVA; INTERVENCION PSICOLOGICA; DIVERSIDAD IDENTITARIA